Pelatihan dan Simulasi Peranan Masyarakat Nunsui Terhadap Mitigasi Bencana Alam - Mooy, Merzy; Seran, Engelbertha Noviani Bria; Fernandez, Wenceslaus Reinaldo (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM Universitas Respati Indonesia), 2026)
There have been several major natural disasters that have attacked Kupang City in the last five years, namely the Seroja tropical cyclone disaster, a 5.1 Magnitude earthquake, and a moving mountain disaster. With several disasters that occur quite often in NTT Province, especially Kupang City, it is undeniable that this has been predicted and warned by BMKG to the Community. This proves that the Community can be said to be unprepared to face and mitigate natural disasters that will occur. Therefore, based on this background, a Community Service activity was held in the form of Natural Disaster Mitigation Training and Simulation in one of the locations in Kupang City, namely the Nunsui, Oesapa Village. The training materials that will be provided are in the form of natural disaster mitigation (before, during, and after it occurs) from three examples of civil engineering fields, namely construction, transportation, and cost management. It is hoped that with the training and simulation activities, the community can understand how dangerous the disaster that might hit the inhabited area is, and the community can respond better to the intended disaster mitigation methods